In pursuit of objective dry eye screening clinical techniques. Issue 1 (December 2016) - Kanellopoulos, Anastasios; Asimellis, George
Abstract Dry eye is a multifactorial, progressive, and chronic disease of the tears and ocular surface. The disease is multi-factorial and has intermittent symptoms. Discomfort, visual disturbance, tear film instability with potential damage to the ocular surface, and increased tear film osmolarity are known associates. Dry eye is a common clinical problem for eye-care providers worldwide and there is a large number of clinical investigative techniques for the evaluation of dry eye. Despite this, however, there is no globally accepted guideline for dry eye diagnosis and none of the available tests may hold the title of the 'gold standard'. The majority of the techniques involved in the diagnosis of the disease, particularly for its early stages, has a large degree of subjectivity. The purpose of this article is to review existing dry eye investigative techniques and to present a new objective dry eye screening technique based on optical coherence tomography.